Upaya Kinerja Pemerintah Desa dalam Pelayanan Publik di Desa Kuwolu Kecamatan Bululawang - Nanik Maulidiyah; Slamet Muchsin; Langgeng Rahmatullah Putra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research explores the optimization of village government performance efforts in providing public services in Kuwolu Village, Bululawang District. The main focus of the study is on the adoption of technology, responsiveness to changes in societal values, the implementation of Law Number 25 of 2009 concerning Public Services, and community participation. The research results indicate that the adoption of technology has a positive impact on improving administrative efficiency, although challenges in digital literacy still need to be addressed. Responsiveness to changes in societal values is a critical point in formulating service policies that align with local expectations. Law Number 25 of 2009 provides clear direction, but its implementation requires in-depth understanding and adaptation to local conditions. The improvement of service quality and administrative efficiency remains the main focus, with active community participation as a vital instrument. Cross-sectoral collaboration and institutional cooperation are identified as assets to create synergy in service provision. Inclusive steps through training programs and digital literacy are solutions to overcome disparities and unequal access. This research creates an overview of the performance efforts of village governments in facing the dynamics of public services in the era of digital transformation and changes in societal values. It is hoped that these findings can provide guidance for other village governments in creating effective and responsive public service systems amid contemporary challenges.